Social media or word of mouth: Maintaining a healthy lifestyle during the COVID-19 pandemic in Indonesia - Putri, Kinkin Yuliaty Subarsa; Setiawan, Benni; Fathurahman, Heri (International Journal of Innovative Research and Scientific Studies, 2024)
The purpose of this study is to examine how public opinions about maintaining a healthy lifestyle during the COVID-19 pandemic are influenced by social media and word-of-mouth (WOM). The research method used is a quantitative approach. This research was conducted in Jakarta by collecting data through the distribution of questionnaires to 200 respondents. The respondents were selected through a purposive sampling technique with several characteristics. Hypothesis testing in this study uses multiple linear regression analysis. The findings of this study show that there is a significant influence between social media and WOM on people's healthy lifestyles during the COVID-19 pandemic. This is indicated by the results of the regression equation which shows a positive correlation. In other words, health promotion during the COVID-19 pandemic is influenced by social media and WOM. The study also concluded that during the COVID -19 pandemic, people relied heavily on opinion leaders in their communities and on social media which they followed. This is due to the impact of technological advances. They are used to accessing social media for health information. So the role of WOM is very influential in people's attitudes towards healthy living. This research has implications for the healthy lifestyles of people in Indonesia. In addition, interpersonal WOM communication strategies are important in building a society that values healthy lifestyles after the COVID-19 pandemic.